2021
DOI: 10.1108/jabs-01-2021-0030
|View full text |Cite
|
Sign up to set email alerts
|

Demand or supply shock during the COVID-19 crisis: empirical evidence from public firms in Indonesia

Abstract: Purpose In examining an economic fluctuation, researchers often refer to the theories of impaired access to capital which mostly explain, from the perspective of bank lending supplies, a shock in firm’s access to investment would decrease its capital expenditures and net debt issuance during crisis period. However, some studies show that this is not always the case. A demand shock theory can explain the decrease in firm’s capital expenditures and net debt issuance during crisis period, but there should be no c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…[12] gives a real-life experience that gives a direct Indication of the causal relationship between MSMEs and poverty reduction in Indonesia. Furthermore, [34] This paper overviews the correlation between the extent of MSMEs' usage of Information and Communication Technology (ICT) and poverty rates at Indonesia's regional level.…”
Section: Msme Growth Poverty and Unemploymentmentioning
confidence: 99%
“…[12] gives a real-life experience that gives a direct Indication of the causal relationship between MSMEs and poverty reduction in Indonesia. Furthermore, [34] This paper overviews the correlation between the extent of MSMEs' usage of Information and Communication Technology (ICT) and poverty rates at Indonesia's regional level.…”
Section: Msme Growth Poverty and Unemploymentmentioning
confidence: 99%
“…The coronavirus 2019 (COVID-19) pandemic is inflicting devastating impacts on businesses and the consumption behaviors of people worldwide (Sinamo and Hanggraeni, 2021; Nguyen et al , 2021). In particular, the global economic disruption brought by the pandemic creates a high level of uncertainty and unpredictability in the business environment (Brown et al , 2020; Puyod and Charoensukmongkol, 2021; Charoensukmongkol and Puyod, 2021; Charoensukmongkol and Suthatorn, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the high level of uncertainty and the unpredictability of the business environment during the COVID-19 pandemic serve as the ideal context for studying the effects of the improvisational behavior of salespeople. Unarguably, the pandemic continues to tremendously change and disrupt people’s consumption habits, thereby making customers’ behavior more complex (Sinamo and Hanggraeni, 2021). To date, the impacts of the pandemic have created interrelated social, technological, and structural challenges for sales organizations.…”
Section: Introductionmentioning
confidence: 99%
“…The impacts of the pandemic extend beyond health problems as it also drives a range of other problems centered around, among others, economic fluctuation. For example, Sinamo and Hanggraeni (2021) study revealed that Indonesian firms have been reluctant to invest during the COVID-19 pandemic. The study also concluded that the demand shock has primarily influenced the economic fluctuation due to the pandemic (Sinamo and Hanggraeni, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Sinamo and Hanggraeni (2021) study revealed that Indonesian firms have been reluctant to invest during the COVID-19 pandemic. The study also concluded that the demand shock has primarily influenced the economic fluctuation due to the pandemic (Sinamo and Hanggraeni, 2021).…”
Section: Introductionmentioning
confidence: 99%